Risk Factors of Development of Iron-Deficiency Conditions in Moscow Adolescents - I. N. Zakharova; I. S. Tarasova; V. M. Chernov; E. B. Machneva; S. I. Lazareva; T. M. Vasilyeva (Педиатрическая фармакология)
The article presents data on prevalence structure and causes of iron-deficiency conditions (IDC) in adolescents. The authors describe both literature data and the findings of their own study in the adolescents (n = 337) studying at Moscow comprehensive schools. Iron- deficiency anemia was revealed in 5.3% of the examined adolescents, latent iron deficiency — in 17%; vast majority of the last were females. The authors also determined the most common causes of IDC development in adolescents: growth spurt (according to the anamnesis), a source of chronic blood loss (prolonged and abundant menstruations [in girls], frequent nasal bleeding), vegetarianism, intense physical activity, diet compliance, excess weight, and obesity.